Building an Unmanned Aerial Vehicle for Humanitarian Aid Delivery - Atar Fuady Babgei; Heri Suryoatmojo (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2020)
When an emergency occurs, immediate responses are needed for the affected areas. Conventional means of transportation often face difficulties carrying supplies to the location in need, especially in severely damaged areas.In this project, a small semi-autonomous unmanned aerial vehicle (UAV) was designed and constructed to undertake a representative humanitarian aid mission. The system has a novel hex-rotor design with overlapping propellers. Half of the motors have been turned upside down with a slight overlap between each propeller, hence reducing the total dimension of the system without losing its efficiency. The system is also equipped with a new lightweight servo activated two ring release system, allowing it to carry and release two kilograms of payloads with only small physical force needed.Overall, the system is capable to operate automatically while performing a series of tasks such as navigate waypoints and deliver payloads before returning to base. the system created in this project could deliver two individual payloads of 1 kg each to the pre-destinated target almost autonomously. The system provided promising results that encourage the utilization of UAV for delivering Humanitarian Aid.